Exponential and infinitary divisors - Lelechenko, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study several problems in the field of modified divisors; more precisely, from the theory of exponential and infinitarydivisors.We analyze the behavior of modified divisors, sum-of-divisors, and totient functions. Our main results are connectedwith the asymptotic behavior of mean values and explicit estimates of the extremal orders.